Calcium and Phosphorus Levels in Nigerian Guinea Fowls - Onyeanusi, B.I. (International Journal of Poultry Science, 2007)
The plasma levels of calcium and phosphorus were analyzed for a period of 12 months using 480 adult female guinea fowls. The calcium levels ranged between 2.00 and 12.25 mg/100ml. The highest level, 12.25 mg/100ml, was recorded in the month of August while the lowest level, 2.0 mg/100ml, was in March. The phosphorus levels ranged between 4.5 and 9.6 mg/100ml. Variation in phosphorus levels was not seasonally dependent as was observed with calcium levels. Statistically, the calcium concentration was significantly (p0.05). The calcium level, therefore, has a direct effect on the reproductive performance of the guinea fowl while the phosphorus level does not.